A simple beam model to analyse the durability of adhesively bonded tile floorings in presence of shrinkage - S. de Miranda; A. Palermo; F. Ubertini (Fracture and Structural Integrity)
A simple beam model for the evaluation of tile debonding due to substrate shrinkage is presented. The tile-adhesive-substrate package is modeled as an Euler-Bernoulli beam laying on a two-layer elastic foundation. An effective discrete model for inter-tile grouting is introduced with the aim of modelling workmanship defects due to partial filled groutings. The model is validated using the results of a 2D FE model. Different defect configurations and adhesive typologies are analysed, focusing the attention on the prediction of normal stresses in the adhesive layer under the assumption of Mode I failure of the adhesive.